2014
DOI: 10.1097/hjh.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Methodological quality of meta-analyses on the blood pressure response to exercise

Abstract: Numerous meta-analyses have been conducted to summarize the growing numbers of trials addressing the effects of exercise on blood pressure (BP), yet it is unclear how well they have satisfied contemporary methodological standards. We applied an augmented version of the Assessment of Multiple Systematic Reviews (AMSTARExBP) scale to 33 meta-analyses retrieved from searches of electronic databases. Qualifying reports used meta-analytic procedures; examined controlled exercise training trials; had BP as a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 63 publications
4
54
0
3
Order By: Relevance
“…In contrast, Johnson et al, 32 included meta-analyses that examined the BP response to exercise as a primary outcome. Johnson et al, identified and later excluded 4 of the reviews included by the Lifestyle Work Group because it was a systematic review (not a meta-analysis) 30 and 3 did not focus on BP as the primary outcome 22,27,28 ; in addition to the reviews included in the Lifestyle Work Group's sample, Johnson et al, identified 10 additional meta-analyses, 2 of which were excluded for "poor" quality.…”
Section: Frequencymentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, Johnson et al, 32 included meta-analyses that examined the BP response to exercise as a primary outcome. Johnson et al, identified and later excluded 4 of the reviews included by the Lifestyle Work Group because it was a systematic review (not a meta-analysis) 30 and 3 did not focus on BP as the primary outcome 22,27,28 ; in addition to the reviews included in the Lifestyle Work Group's sample, Johnson et al, identified 10 additional meta-analyses, 2 of which were excluded for "poor" quality.…”
Section: Frequencymentioning
confidence: 96%
“…32 The full search details have been reported elsewhere, 32 but briefly, our literature search was inclusive, encompassing all meta-analyses from the earliest coverage until 2013, a search that yielded 33 meta-analyses. On average, the study quality of this literature was fair, with numerous methodological deficiencies including (1) detail of the search strategies was insufficient for replication of the search, (2) only half of the meta-analyses integrated duplicate study selection and data extraction, and (3) the majority failed to document the quality of the included studies or examine whether study quality influenced the primary result (ie, magnitude of the BP change).…”
Section: Reasons For Different Fitt Ex R X Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Além de prevenir o desenvolvimento da HAS (43), o aumento da atividade física, seja ela por treinamento ou por mudança dos hábitos de vida diária, reduz os níveis de pressão arterial de pacientes hipertensos, guardadas as devidas proporções de cada uma das práticas (44).…”
Section: Treinamento Aeróbio (Ta)unclassified